Diseño y simulación de una planta para la producción de biodiésel a partir de Jatropha curcas L. en el departamento de Bolívar (2015)
In recent years biofuels have been studied as a good alternative instead of fossil fuels. Jatropha curcas L oil (J. curcas)is a feedstock used to produce biodiesel which does not affect food security, has good yields and more advantages than traditional oils. Therefore, in this work, a conceptual design of a biodiesel production from J. curcas was developed by simulation, using HYSYS® software. A case study was proposed to produce biodiesel from 11000kg/h of Jatropha oil. Sequential stages of esterification and transesterification were studied due to high content of free fatty acid (FFA) in the oil. Thermodynamic data of the components was obtained from several models, which allowed to obtain a biofuel with high content of methyl esters over 98% (mass). Oil and biodiesel properties estimated by simulations and theoretical correlations showed a good fit with experimental data reported by different authors, and international standards for biodiesel such us ASTM D6751 and EN-12214 that helps to identify the J. curcas as a viable alternative to produce biofuels, also it could be suggested a commercial scale implementation in the department of Bolivar, because alimentary food would not been affected and it encourages to produce biodiesel from alternative resources in Colombia.